Approximation of Analytic Functions by Chebyshev Functions - Soon-Mo Jung; Themistocles M. Rassias (Abstract and Applied Analysis)
We solve the inhomogeneous Chebyshev's differential equation and apply this result for approximating analytic functions by the Chebyshev functions.